Clinical Characteristic of Patients Underwent Bone Mineral Density Examination in Prof. Dr. R. Soeharso Orthopaedic Hospital in 2022-2023: A Cross-Sectional Study - R. Andhi Prijosedjati; Pamudji Utomo; Leli Sabariyah; Ahmad Fauzi (Journal Orthopaedi and Traumatology Surabaya)
Background: In Indonesia, osteoporosis affects roughly 23% of men and women aged 50-70 and a staggering 53% of those over 70. Understanding the characteristics of patients undergoing bone mineral density (BMD) examinations is crucial for developing better strategies for prevention, diagnosis, and treatment. This study investigates the characteristics of patients who had BMD examinations at the Prof. Dr. R. Soeharso Orthopaedic Hospital.